Chemical prestressing of high-performance concrete reinforced with CFRP tendons. (1st May 2020) - Wyrzykowski, Mateusz; Terrasi, Giovanni; Lura, Pietro
Abstract: Chemical prestress (self-prestress) is a process, in which expansion of concrete with special additives can be used to generate tension in the reinforcement and prestress in the concrete. Until now, the prestress levels that could be reached with this technique were usually lower than with traditional (external) prestressing. With the new family of expansive high-performance concretes (HPC) developed by us, very high levels of residual expansion can be achieved without compromising the durability and still reaching very good mechanical properties of the concrete. In this paper, we combine the expansive HPC with tendons made of ultra-high modulus (>400 GPa) carbon fiber reinforced polymers (CFRP). Through the expansion of the concrete and its bond with the sand-coated tendons, we could introduce tensile stresses of more than 600 MPa in the tendons (for 1% reinforcement ratio), corresponding to more than 4 MPa compressive stress (prestress) in the concrete. 4-Point bending tests show that the chemical prestress increased the cracking moment of slender concrete beams more than three times compared to the reference concrete. Our long-term tests of the strains of the tendons show that the losses of prestress due to shrinkage and compressive creep are very low.